Bacteriological , serological and som antibiotics study of Typhoid fever in Baghdad province: AL-Mezrakje A.s and AL-Shaheen z.kh - s., AL-Mezrakje A. (The Iraqi Journal of Veterinary Medicine, 2008)
Two hundreds suspected typhoid fever patients blood and stool sampleswere collected. The diagnosis of patients was concerned with the clinicalsymptoms and serologically obtained from Widal test by using both H,Oantigens.The titer of antibodies were concentrated at a levels 80, 160 againsteach antigens. Typhoid fever infect both sex, but the rate of infection amongmales was higher (54%) as compared with that of females (46%), while thehighest rate of infection was encountered among the age 15-29 years old inmales and females 24.5%, 17.5% respectively. Sixty one isolates ofSalmonella typhi were isolated from the blood and feces specimens (49,12)respectively. Serological characterization of isolates showed that 49 isolatesbelong to 9,12-Vi-d serotype and 12 isolates to 9,12-d serotype.The antibiogram pattern against Salmonella typhi cultures showed differentresults. The majority of isolates were sensitive to Streptomycin, Rifampicin,Chloramphenicol, Gentamycin and Cephalexin and resistant to bothPenicillin and Erythromycin.